Comparison of occlusal discomfort in patients with temporomandibular disorders between myofascial pain and disc displacement - Toshihisa Shibuya; Koji Kino; Masashi Sugisaki; Fumiaki Sato; Tadasu Haketa; Akira Nishiyama; Michiko Takaoka; Takenobu Ota; Takayuki Ishikawa; Noriyuki Narita (Journal of Medical and Dental Sciences, 2009)
We compared occlusal discomfort in patients with temporomandibular disorders (TMD) between myofascial pain (MFP) and disc displacement (DD) using a database created from Sep, 2003 to Aug, 2005. We selected 71 patients with MFP and 170 patients with DD to construct a null model of structural equation modeling (SEM) in which anxiety influenced depressive mood, depressive mood aggravated occlusal discomfort and sleep complaints, and sleep complaints or an onset event caused by another person aggravated occlusal discomfort. We performed a simultaneous analysis of patients with MFP and DD. The estimated parameter of the path from depressive mood to occlusal discomfort was significant for patients with MFP, but not for patients with DD. The path from an onset event caused by another person, such as dental treatment to occlusal discomfort was significant in patients with MFP and those with DD. The Goodness of Fit Index (=0.909), The Adjusted Goodness of Fit Index (=0.867), and The Root Mean Square Error of Approximation (=0.039) indicated good acceptability. These results suggested that an increase in depressive mood may aggravate occlusal discomfort in patients with MFP, and an onset event caused by another person, such as dental treatment, also may aggravate occlusal discomfort in patients with MFP and those with DD.